The Synergistic Effect of Ketoconazole and Probiotic Bifidobacterium Bifidum on Isolated Composition of Expression of Candida Albicans Als Gene Biofilm from Oral Samples - Mina Rezaei; Sedigheh Mehrabian; Kiumars Amini (Tehran University of Medical Sciences, 2020)
Background and Aim: Candida albicans has numerous virulence factors such as the agglutinin-like sequence(ALS) genes which code the large glycoprotein family that has a role in the adherence of Candida. The present study was to observe the synergistic effect of ketoconazole and probiotic composition of Bifidobacterium bifidum on expression of C. albicans als gene biofilm isolated from oral samples. Materials and Methods: In this cross-sectional study, 12 clinical isolates of C. albicans were collected from oral periodontal infection in patients referred to dental clinic in Kerman. The MIC and FIC values for each treatment(keto and probiotic alone and keto-probiotic composition) were obtained using micro broth dilution method. Finally, a real-time PCR test was performed to evaluate the level of ASL gene expression in the strains and the results were analyzed using the 2-ΔΔct  method. Results: The results showed that the combination of ketoconazole and bifidobacterium bifidum had synergistic effects. The results of this study showed that the effect of Ketoconazole(keto), B.bifidum(probiotic) alone and the effects of ketoconazole+Bifidobacterium(keto+pro) were 1.47, 1.61 and 1.29 times, reduced the als gene, respectively. Conclusion: The results of this study showed that synergistic effects between ketoconazole and probiotic B. bifidum have been shown to reduce als gene expression(biofilm production). Therefore, it is recommended to administer probiotic supplementation with ketoconazole in the treatment of candidal infections.